Probing the supramolecular features via π–π interaction of a di-iminopyrene-di-benzo-18-crown-6-ether compound: experimental and theoretical study. Issue 63 (16th October 2020) - Coroaba, Adina; Isac, Dragos-Lucian; Al-Matarneh, Cristina; Vasiliu, Tudor; Ibanescu, Sorin-Alexandru; Zonda, Radu; Ardeleanu, Rodinel; Neamtu, Andrei; Timpu, Daniel; Nicolescu, Alina; Mocci, Francesca; Maier, Stelian S.; et al.
Abstract : Herein, we report the formation of a potential supramolecular arrangement mediated by inter- and intra-molecular interactions between di-iminopyrene-dibenzo-18-crown-6-ether molecules. Abstract : A novel DPyDB-CN-18C6 compound was synthesised by linking a pyrene moiety to each phenyl group of dibenzo-18-crown-6-ether, the crown ether, through –HCN– bonds and characterized by FTIR, 1 H-NMR, 13 C-NMR, TGA, and DSC techniques. The quantitative 13 C-NMR analysis revealed the presence of two position isomers. The electronic structure of the DPyDB-CN-18C6 molecule was characterized by UV-vis and fluorescence spectroscopies in four solvents with different polarities to observe particular behavior of isomers, as well as to demonstrate a possible non-bonding chemical association (such as ground- and excited-state associations, namely, to probe if there were forming dimers/excimers). The interpretation of the electronic structure was realized through QM calculations. The TD-CAM-B3LYP functional, at the 6-311+G(d, p) basis set, indicated the presence of predominant π → π* and mixed π → π* + n → π* transitions, in line with the UV-vis experimental data. Even though DPyDB-CN-18C6 computational studies revealed a π-extended conjugation effect with predominantly π → π* transitions, thorough fluorescence analysis was observed a weak emission, as an effect of PET and ACQ. In particular, the WAXD analysis of powder and thin films obtained from n -hexane, 1, 2-dichloroethane, and ethanol indicated an amorphous organization, whereas from toluene a smectic ordering was obtained. These results were correlated with MD simulation, and it was observed that the molecular geometry of DPyDB-CN-18C6 molecule played a defining role in the pyrene stacking arrangement.